The wonder world of the seashore - Neurath, Marie (London M. Parrish, 1961)
Describes curious creatures of sand and sea such as the hermit crab with an anemone roommate, the crab that never goes out, and worms that look like flowers.
Keywords: Seashore biology -- Juvenile literature; Marine biology